2020
DOI: 10.1210/clinem/dgaa343
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in 11-Oxygenated Androgen Patterns Across Adulthood

Abstract: Abstract Context The gonads are the major source of sex steroids during reproductive ages. The gonadal function declines abruptly in women and gradually in men. The adrenals produce 11-oxygenated androgens (11-oxyandrogens), which start rising during adrenarche. Following menopause, 11-oxyandrogens levels remain similar to reproductive ages. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 25 publications
5
36
3
Order By: Relevance
“…We found that the 11-oxygenated androgen precursors 11OHA4 and 11KA4 persist after castration and correlate with 11KT. The concentrations detected in our patients without exogenous glucocorticoid treatment are comparable to previously reported concentration of 11OHA4 and 11KA4 in elderly men (17). In line with previous reports, we found that 11OHA4 is the most abundant 11-oxygenated androgen in the circulation, with a median concentration of 2.7 nmol/L (0.48 -5.1 nmol/L) in all CRPC patients, and 4.96 nmol/L (3.05 -6.13 nmol/) in patients who did not receive exogenous glucocorticoid treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the 11-oxygenated androgen precursors 11OHA4 and 11KA4 persist after castration and correlate with 11KT. The concentrations detected in our patients without exogenous glucocorticoid treatment are comparable to previously reported concentration of 11OHA4 and 11KA4 in elderly men (17). In line with previous reports, we found that 11OHA4 is the most abundant 11-oxygenated androgen in the circulation, with a median concentration of 2.7 nmol/L (0.48 -5.1 nmol/L) in all CRPC patients, and 4.96 nmol/L (3.05 -6.13 nmol/) in patients who did not receive exogenous glucocorticoid treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The adrenal-derived steroid 11-ketotestosterone (11KT) is of particular interest, as it is one of a few endogenous steroids capable of activating the AR at sub-nanomolar concentrations, similar to T and DHT (13)(14)(15). In healthy adult men, circulating T concentrations exceed those of 11KT (16,17). During ADT, gonadal steroidogenesis is inhibited and T concentrations typically fall below 0.5 nmol/L (18), which is lower than 11KT concentrations in healthy men (16).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown that 11KT circulates at similar or higher levels than T in healthy women and represents the predominant circulating androgen in androgen-excess conditions such as polycystic ovary syndrome and congenital adrenal hyperplasia ( 7-10 ). Moreover, unlike classic androgens, circulating levels of 11-oxygenated androgens appear not to decline after menopause ( 8 , 11 ).…”
mentioning
confidence: 99%
“…However, when assessing the effect of age on androgen activation in peripheral tissues, age-related changes in the supply of androgen precursors from circulation need to be considered, in addition to age-dependent changes in the expression of androgen-activating and -inactivating enzymes in the peripheral target tissues of androgen action. While circulating levels of classic androgens significantly decline with age, levels of 11-oxygenated androgens remain constant across adulthood (29,30). Hence, the peripheral activation of 11-oxygenated androgens is favored over the activation of classic androgens not only by the substrate preference of the key androgen activating enzyme AKR1C3, but also by constant high substrate availability across the life span.…”
Section: Discussionmentioning
confidence: 99%